Peace in everyday relationships - Sirug, Winston S. (Manila, Philippines : Mindshapers Co. Inc., 2008)
This book has been written to provide the essential concepts and skills of algebra, and for further study in mathematics. Thus, one of the major objectives of the book is to make a comfortable transition from basic mathematics to other more advance mathematics courses of the students.
Chapter 1. Sets -- Chapter 2. Real Numbers -- Chapter 3. Equations and Inequalities -- Chapter 4. Exponents and Polynomials -- Chapter 5. Factoring Polynomials -- Chapter 6. Rational Expressions -- Chapter 7. Radicals -- Chapter 8. Linear Relations and Functions -- Chapter 9. Systems of Linear Equations and Inequalities -- Chapter 10. Quadratic Equations -- Chapter 11. Exponential and Logarithmic Functions -- Chapter 12. Sequences and Series.
Includes index.
Keywords: ALGEBRA -- MATHEMATICS